Xeno-free alternatives to the use of fetal bovine serum in head and neck cancer explant culture - Azhakesan, Alexya; Seiz, Elena; Kern, Johann; Hendricks, Laura; Fleckenstein, Jens; Jungbauer, Frederic; Ludwig, Sonja; Brochhausen, Christoph; Bugia, Luis; Scherl, Claudia; Lammert, Anne; Rotter, Nicole; et al. (Alternatives to laboratory animals, 2025)
Patient-derived head and neck squamous cell carcinoma (HNSCC) explant models have been shown to retain the original tumour microenvironment and morphological characteristics. To enhance the human relevance of models and improve clinical outcomes, there is an emerging move toward preclinical models that are cultured in xeno-free media (i.e. media containing no non-human animal-derived components). Fetal bovine serum (FBS) has been the standard cell culture medium supplement in most in vitro systems. However, growing emphasis on ethical concerns, animal welfare considerations and reproducibility, as well as the need to implement the Three Rs principles, have driven substantial efforts to identify viable xeno-free alternatives to FBS. In this study, an ex vivo culture model for HNSCC was developed, based on the use of xeno-free media. Human platelet lysate (hPL)-supplemented medium and a commercially available xeno-free human mesenchymal stromal cell (MSC) expansion medium were evaluated, comparing HNSCC explant model growth to that in the ‘standard’ FBS-supplemented medium, over a 10-day culture period. To best reflect clinical conditions, the tissues were treated with radiochemotherapy (RCT) comprising cisplatin and fractionated irradiation. After 10 days, the tissues were formalin-fixed, paraffin-embedded, and assessed for the expression of key biomarkers, including PD-L1, Ki-67 and vimentin. The upregulation of PD-L1, as well as the downregulation of Ki-67 and vimentin, were consistent across all media, thus validating hPL-supplemented medium and MSC medium as viable alternatives to FBS-supplemented medium, for use in the culture of humanised HNSCC preclinical models.
Gesehen am 26.08.2025
Erstmals online veröffentlicht: 19. Juni 2025